Early-Lethal Costello Syndrome Due to Rare HRAS Tandem Base Substitution (c.35_36GC>AA; p.G12E)–Associated Pulmonary Vascular Disease. (November 2014) - Weaver, K. Nicole; Wang, Dehua; Cnota, James; Gardner, Nicholas; Stabley, Deborah; Sol-Church, Katia; Gripp, Karen W.; Witte, David P.; Bove, Kevin E.; Hopkin, Robert J.
Costello syndrome is a rare, autosomal-dominant syndrome caused by activating missense mutations in the Harvey rat sarcoma viral oncogene homolog ( HRAS ), most often p.G12S. Several rare mutations have consistently been associated with a more severe phenotype that is often lethal in infancy. Cause of death is most often respiratory failure, with hypertrophic cardiomyopathy playing a significant role in morbidity. Impaired fibroblast elastogenesis is thought to contribute to the Costello phenotype, but reports of histologic evidence of disordered elastogenesis at autopsy are limited. We report a patient with Costello syndrome due to a rare tandem base substitution (c.35_36GC>AA) resulting in the p.G12E missense change. The proband died at the age of 3 months from respiratory failure, with minimal evidence of cardiomyopathy. The autopsy disclosed pulmonary vascular dysplasia affecting small arteries and veins associated with abnormal elastin distribution in tortuous dilated arteries and veins, with nonuniform wall thickness and semiobstructive lesions at artery branch points typical of early pulmonary hypertensive vascular disease. Elastic fibers in the dermis were abnormally short and fragmented. This case suggests that disordered elastogenesis in the pulmonary vasculature and undiagnosed (or underdiagnosed) pulmonary hypertension may contribute to morbidity in patients with Costello syndrome.